Homoharringtonine Inhibits Allergic Inflammations by Regulating NF-κB-miR-183-5p-BTG1 Axis - Kim, Misun; Jo, Hyein; Kwon, Yoojung; Kim, Youngmi; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Pharmacology, 2020)
Homoharringtonine (HHT) is a drug for treatment of chronic myeloid leukemia. However, the role of HHT in allergic inflammations remains unknown. Mouse model of atopic dermatitis (AD) induced by 2, 4,-dinitroflurobenzene (DNFB) and anaphylaxis employing 2,4-dinitropheny-human serum albumin (DNP-HSA) were used to examine the role of HHT in allergic inflammations. HHT inhibited in vitro allergic reactions and attenuated clinical symptoms associated with AD. DNFB induced features of allergic reactions in rat basophilic leukemia (RBL2H3) cells. HHT suppressed effect of AD on the expression of Th1/Th2 cytokines. HHT inhibited passive cutaneous anaphylaxis and passive systemic anaphylaxis. MiR-183-5p, increased by antigen stimulation, was downregulated by HHT in RBL2H3 cells. MiR-183-5p inhibitor suppressed anaphylaxis and AD. B cell translocation gene 1 (BTG1) was shown to be a direct target of miR-183-5p. BTG1 prevented antigen from inducing molecular features of in vitro allergic reactions. AD increased the expression of NF-kB, and NF-kB showed binding to the promoter sequences of miR-183-5p. NF-kB and miR-183 formed positive feedback to mediate in vitro allergic reactions. Thus, HHT can be an anti-allergy drug. We present evidence that NF-κB-miR-183-5p-BTG1 axis can serve as target for development of anti-allergy drug.